It is asking you to find the sum of k^2 - 1 from k=1 to k=4. Since that is only 4 numbers, calculating the sum by hand wouldn’t be that bad.
(1^2 - 1) + (2^2 - 1) + (3^2 - 1) + (4^2 - 1) = 26
The easier way to find the sum is to use a few simple formulas.
When we have a term that is just a constant c, the formula is c*n.
When we have a variable k, the formula is k*n*(n+1)/2.
When we have a squared variable, the formula is k*n*(n+1)*(2n+1)/6.
In this case, we have a squared variable k^2 and a constant of -1.
So plug in n=4 to the formulas:
4*5*9/6 - 1*4 = 26
The answer is 26